Simulation of Stress Distribution and Deformation Analysis for Cantilever I-beams Using ABAQUS Software. (September 2019) - Runsheng, Wen; Yang, Zhang
Abstract: In this paper, the stress distribution of the I-beam cantilever beam is simulated by ABAQUS software, and the uniform load increases with time on the surface of the I-beam to observe the position of the maximum stress and the deformation of the right end.